ANALYSIS OF THE RELATIONSHIP BETWEEN IMPLEMENTATION OF STBM PROGRAM AND REDUCTION OF STUNTING’S RISK FACTORS IN CHILDREN UNDER TWO YEARS OLD IN PALEMBANG - Fadilah, Mariatul; Novita, Emma; Roflin, Eddy; Syakurah, Rizma Adlia; Pariyana, .; Irene, Angela (Advances in Social Sciences Research Journal, 2020)
Abstract Stunting, a condition of major nutritional deficiency in Indonesia, is a nutritional problem during the first 1000 days of life, from the first day of pregnancy to the age of 2 years. Many studies link poor environmental sanitation to the incidence of stunting. To improve environmental sanitation, the Government of Indonesia issued Minister of Health Regulation No. 3 of 2014 in the form of a Community-Based Total Sanitation (STBM) program. STBM is carried out in 5 pillars, namely stopping open defecation (SBABS), washing hands with soap (CTPS), managing drinking water and household food (PAMMRT), protecting household waste (PSRT), and protecting household liquid waste ( PLCRT). This study aims to analyze the knowledge of the successful implementation of the STBM program with the risk factors for stunting of children under two years of age in the city of Palembang. This type of research, analytic observational, and cross-sectional study design. Primary data were collected directly using a questionnaire. The average level of knowledge about STBM pillars and risk factors for stunting is in a good category. There is a significant relationship (p-value <0.05) between knowledge of SBABS and risk factors for infection in children, environmental sanitation, and availability of clean water; CTPS with risk factors for infection in children and the availability of clean water; PAMMRT with risk factors for infection in children and the use of biomass fuels; PSRT with risk factors for infection in children and environmental sanitation; and PLCRT with risk factors for infection in children, environmental sanitation and availability of clean water. It is concluded that the pillars of PSRT and PLCRT have the most influence on the risk factors for stunting in Palembang City.